(untitled) (Nigerian Journal of Technology, 2015)
This paper examines the effect of iron content and plastic deformation on the mechanical properties of wrought Al-Fe-Si alloy. Seven samples each of dimension 240mm x 140mm x 7mm were cast for each aluminium alloy plate containing iron content of 0.708%, 0.909% and 0.931% by chill casting method. As-received commercial aluminium alloy 8011 has an iron content of 0.857% and it was cut into seven samples of the same geometry. Cold rolling experiment was carried out from 30% to 80% reduction in thickness. The mechanical properties of the alloys were investigated. The results showed that the maximum ultimate tensile strength obtained for alloys 0.708%Fe and 0.857%Fe were 171.45MPa and176.45MPa respectively both occurred at 60% reduction in thickness while alloys 0.909%Fe and 0.931%Fe respectively have 163.16MPa and 170.00MPa at 80% reduction in thickness. An increase in iron content led to corresponding decrease in tensile strength but at 80% reduction in thickness, the strength increase with iron content for alloys of 0.9%Fe and above. The micro-vicker hardness values increases, reaching the peak and then decreases with increasing percentage deformation. http://dx.doi.org/10.4314/njt.v35i1.19